Effect of Dietary Oregano (Lippia origanoides) and Clover (Eugenia caryophillata) Essential Oilsʼ Formulations on Intestinal Health and Performance of Pigs - Dieguez, Susana Nelly; Decundo, Julieta María; Martínez, Guadalupe; Amanto, Fabián Andrés; Bianchi, Carolina Paula; Pérez Gaudio, Denisa Soledad; Soraci, Alejandro Luis (Planta Medica, 2021)
The incorporation of natural essential oils to the pigsʼ diet in intensive production systems is a potential tool to improve gut health and prevent infections without using antibiotics. Nevertheless, different products, even containing the same compounds, coming from the same botanical species, may exert dissimilar biological effects due differences in the technological processes by which they are produced and preserved. For this reason, suitability of a given product based on natural extracts, intended for swine production must be thoroughly evaluated. In the present study, we assessed the effects of three additives containing oregano (Lippia origanoides) essential oil, alone or in combination with clover (Eugenia caryophillata) essential oil, with or without being microencapsulated, on gastrointestinal health and on some performance parameters in a commercial pig production farm. Recently weaned piglets were randomly divided in four groups, and basal diet or essential oil-supplemented diet (OCE; MOCE; MOE) was randomly assigned to each of the groups from weaning to finishing. Blood samples were collected at pre-established days after weaning. Intestinal sampling took place at 42 and 72 days of age. Pigs consuming the supplemented diets showed higher intestinal metabolic activity during the post-weaning period, decreasing the impact of weaning stress on enterocytesʼ metabolism. Intestinal barrier function was not affected in pigs consuming microencapsulated products. All treated groups showed improved intestinal architecture, increased digestive enzymes activity and caecal VFA concentrations. The incorporation of the dietary essential oils products brought beneficial effects on gastrointestinal health that were reflected in improved performance parameters.
Keywords: essential oils; intestinal health; pigs; Lippia origanoides; Eugenia caryophillata